LAND VOLUME ESTIMATION AND CUT AND FILL PROCESS TIME ESTIMATION THROUGH TILE BASED TERRAIN LAND MODELING - HAYAT (NIM: 23207114), LATIFUL
ABSTRACT: Housing development is done by passing several processes, these are topographic mapping, site planning, grading plan modeling, cut and fill processing, stacking out and building houses or others. Before the process of cut and fill is done, grading plan have to be analyzed to determine the soil volume needed to fill the land and to disposed. Large scale residential area projects are sometimes demanding a quick settlement, so the used of heavy equipments' are required. The time required to finish cut and fill process is influenced by several factors such as the amount of soil that needs to be moved, to be cut and to be filled. The other factor that influence is the production capacity of heavy equipments. Residential Area Design (RAD) is an application that helps developers making a virtual mock. The problems discussed in this research are how to estimate the land volume based on the initial condition of the land toward grading plan using grid method volume through tile based terrain visualization. Also how to estimate the time to finish cut and fill process based on the amount of soil volume by using several heavy equipments in particular RAD application. Estimation in this research is limited on some issues, such as: tile based terrain model formed in RAD application, heavy equipments production capacity that are calculated based on their datasheets, and another restrictions described in the limitation problem in chapter one. The result of this research shown that the volume estimation of cut and fill soils can be calculated by comparing volume between the current land volume and grading plan volume in each tile. Volume estimation in each tile is calculated based on the principle of a simple building space calculation. Cut and fill process estimation time is determined by the estimation of cut and fill soil volume, followed by a calculation of the heavy equipment, production capacities. It can be calculated through the heavy equipment manufacturer datasheets, or by physical condition that can be measured with certain equality.